Evaluate the sum $\frac{1}{3^1} + \frac{2}{3^2} + \frac{3}{3^3} + \cdots + \frac{k}{3^k} + \cdots $

How would I go about solving this problem? I'm thinking of setting the sum to $S$, multiplying by $3$, and then subtracting from the original equation. HELP!

I have explained my reasoning in the comment below.

  • $\begingroup$ Your idea seems good... What did it lead to? $\endgroup$ – vrugtehagel Mar 10 '18 at 22:59
  • 5
    $\begingroup$ Let the sum be $S$. This series looks almost geometric, but not quite. We can turn it into a geometric series as follows: \begin{align*} S &= \frac{1}{3^1} +\frac{2}{3^2} + \frac{3}{3^3} + \frac{4}{3^4} + \cdots \\ \frac{1}{3}S &= \frac{0}{3^1} + \frac{1}{3^2} + \frac{2}{3^3} + \frac{3}{3^4} + \cdots \\ \frac{2}{3}S = S - \frac{1}{3}S &= \frac{1}{3^1} + \frac{1}{3^2} + \frac{1}{3^3} + \frac{1}{3^4} + \cdots \end{align*}Now, we do have a geometric series, so we can find $\frac{2}{3}S = \frac{\frac{1}{3}}{1 - \frac{1}{3}} = \frac{1}{2}$, and $S = \boxed{\frac{3}{4}}$. $\endgroup$ – A Piercing Arrow Mar 10 '18 at 23:02
  • $\begingroup$ That looks good! You basically had the answer already ;) $\endgroup$ – vrugtehagel Mar 10 '18 at 23:04
  • $\begingroup$ This is an arithmetico-geometric sequence: en.wikipedia.org/wiki/Arithmetico%E2%80%93geometric_sequence $\endgroup$ – an4s Mar 10 '18 at 23:19
  • 3
    $\begingroup$ Is it too much to ask you to write what you wrote in a comment, in the actual question you posted? $\endgroup$ – Namaste Mar 10 '18 at 23:32

So as you said, let's set

$$S=\frac{1}{3^1} + \frac{2}{3^2} + \frac{3}{3^3} + \cdots + \frac{k}{3^k}\cdots$$

Now we see

$$3S=\frac{1}{3^0} + \frac{2}{3^1} + \frac{3}{3^2} + \cdots + \frac{k}{3^{k-1}}\cdots$$

And so

$$3S-S=\frac{1-0}{3^0} + \frac{2-1}{3^1} + \frac{3-2}{3^2} + \cdots + \frac{k-(k-1)}{3^{k-1}}\cdots$$ or, rewritten,


So that we get $S=\frac 34$.

  • $\begingroup$ So I was correct! Thank you. $\endgroup$ – A Piercing Arrow Mar 10 '18 at 23:05
  • $\begingroup$ Yup, you were! Be sure to accept one of the answers so that this question doesn't end up in the unanswered section ;) $\endgroup$ – vrugtehagel Mar 10 '18 at 23:06

Nice approach. You can also do this as follows and this method is useful for other types of series too. Compute the following sum $$f(x)=\sum_{k\geq 1}\left(\frac{x}{3}\right)^k$$ And then compute the derivative of $f$ and evaluate $f'(1)$.


Note that $$ \sum_{k=1}^\infty \frac{k}{3^k}=\sum_{k=1}^\infty \sum_{j=1}^k\frac{1}{3^k} =\sum_{j=1}^\infty \sum_{k=j}^\infty\frac{1}{3^k} =\sum_{j=1}^\infty\frac{1/3^j}{2/3} =\frac{3}{2}\frac{1/3}{1-(1/3)} =\frac{3}{4} $$ where the interchanging of summation is allowed since we are dealing with non-negative series.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.